Pengaruh Interaksi Live Streaming, Kredibilitas Konten Kreator, Dan Variasi Produk Terhadap Keputusan Pembelian Di Tiktok Shop : Studi Kasus Mahasiswa Kota Palembang - Azzahra, Anggita; Umari, Zuul Fitriani; Riski, Oki Sania (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of live streaming interaction, content creator credibility, and product variety on students’ purchasing decisions on TikTok Shop in Palembang City. The research employed a quantitative approach with purposive sampling involving 96 respondents. Data were analyzed using multiple linear regression with SPSS 26. The results show that the three independent variables significantly affect purchasing decisions both partially and simultaneously. These findings highlight the importance of real-time interaction, credibility of information, and product variety in shaping students’ purchasing behavior in the digital era.